An increased rate of falling leads to a rise in fracture risk in postmenopausal women with self-reported osteoarthritis: a prospective multinational cohort study (GLOW). Issue 6 (23rd June 2012) - Prieto-Alhambra, Daniel; Nogues, Xavier; Javaid, M Kassim; Wyman, Allison; Arden, Nigel K; Azagra, Rafael; Cooper, Cyrus; Adachi, Jonathan D; Boonen, Steven; Chapurlat, Roland D; Compston, Juliet E; Gehlbach, Stephen H; et al.
Abstract : Objectives: Patients with osteoarthritis have increased bone mass but no decrease in fractures. The association between self-reported osteoarthritis and incident falls and fractures was studied in postmenopausal women. Methods: The Global Longitudinal Study of Osteoporosis in Women is a prospective multinational cohort of 60 393 non-institutionalised women aged ≥55 years who had visited primary care practices within the previous 2 years. Questionnaires were mailed at yearly intervals. Patients were classified as having osteoarthritis if they answered yes to the question, 'Has a doctor or other health provider ever said that you had osteoarthritis or degenerative joint disease?', and this was validated against primary care records in a subsample. Information on incident falls, fractures and covariates was self-reported. Cox and Poisson models were used for incident fractures and number of falls, respectively, to compute hazard ratios (HRs) and rate ratios (RRs) for baseline osteoarthritis status. Results: Of 51 386 women followed for a median of 2.9 years (interquartile range 2.1–3.0), 20 409 (40%) reported osteoarthritis. The adjusted HR for osteoarthritis predicting fracture was 1.21 (95% CI 1.13 to 1.30; p<0.0001) and the adjusted RR for falls was 1.24 (95% CI 1.22 to 1.26; p<0.0001). However, the association between osteoarthritis and fracture was not significant after adjustment for incident falls (HR 1.06 (95% CI 0.98 to 1.15; p=0.13)). Conclusions: Postmenopausal women with self-reported osteoarthritis have a 20% increased risk of fracture and experience 25% more falls than those without osteoarthritis. These data suggest that increased falls are the causal pathway of the association between osteoarthritis and fractures.